2015
DOI: 10.1016/j.celrep.2015.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Akt Kinase-Mediated Checkpoint of cGAS DNA Sensing Pathway

Abstract: SUMMARY Upon DNA stimulation, cyclic GMP-AMP synthetase (cGAS) synthesizes the second messenger cyclic GMP-AMP (cGAMP) that binds to the STING, triggering antiviral interferon-β (IFN-β) production. However, it has remained undetermined how hosts regulate cGAS enzymatic activity after the resolution of DNA immunogen. Here, we show that Akt kinase plays a negative role in cGAS-mediated anti-viral immune response. Akt phosphorylated the S291 or S305 residue of the enzymatic domain of mouse or human cGAS, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
164
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(167 citation statements)
references
References 46 publications
(50 reference statements)
2
164
1
Order By: Relevance
“…In this context, we have demonstrated that phosphorylation of Sting at S365 is important for its recruitment of Senp2 at late phase of viral infection. Recently, cGas has been reported to be phosphorylated to turn off its activity (Seo et al, 2015). It is likely that phosphorylation of cGas also plays a role for its recruitment of Senp2 at late phase of viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, we have demonstrated that phosphorylation of Sting at S365 is important for its recruitment of Senp2 at late phase of viral infection. Recently, cGas has been reported to be phosphorylated to turn off its activity (Seo et al, 2015). It is likely that phosphorylation of cGas also plays a role for its recruitment of Senp2 at late phase of viral infection.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we show that deamidation of cGAS by UL37 specifically ablated the cGAMP-synthesizing activity of cGAS. Previous studies have shown that cGAS is subjected to diverse post-translational modifications, including sumoylation, glutamylation and phosphorylation (Cui et al, 2017; Hu et al, 2016; Seo et al, 2015; Xia et al, 2016), and direct antagonism by an array of microbial proteins (Aguirre et al, 2017; Wu et al, 2015; Zhang et al, 2016a). How deamidation, of RIG-I and cGAS, cross-talks with these regulatory mechanisms remain unclear and these potential cross-talks, if exist, will connect protein deamidation to other well-established signaling cascades and expand the functional repertoire of protein deamidation in high eukaryotes.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse maltose-binding protein (MBP)-cGAS fusion protein (141–507) (Seo et al, 2015) was expressed in BL21 (DE3) and bacteria were grown at 37 °C to an OD600 of 0.6. Then, cultures were cooled to 18 °C and pro tein expression was induced by adding 0.1 mM Isopropyl b-D-1-thiogalactopyranoside (IPTG) for 16 h. Cells were collected by centrifugation and lysed with Triton X-100 buffer (20 mM Tris-HCl [pH 7.4], 200 mM NaCl, 10% glycerol, 0.5% Triton X-100, 0.2 mg/ml lysozyme supplemented with protease inhibitor cocktail).…”
Section: Star Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cells have adopted mechanisms to regulate the potent inflammatory IFN-I response, and 2 recent studies describe the inhibitory regulation of cGAS. Reversible glutamylation by tubulin tyrosine ligase-like (TTLL) glutamylases inhibits cGAS synthase and DNA-binding activity [194] , and the phosphorylation of cGAS by Akt 119 dampens its activity [195] . More regulatory mechanisms are likely to be discovered in the future.…”
Section: Dna Sensingmentioning
confidence: 99%